Jenis-Jenis Jamur Pada Saluran Pencernaan Ayam Kampung (Gallus domesticus Linn.) - Rahmawati, Khristaliana Phikly, Siti Khotimah (Jurnal Protobiont, 2015)
Free-range chicken digestion tract (Gallus domesticus Linn.) is one of the survival and the growth of microbes such as fungi, both the beneficial fungi and adverse. The purpose of this study was to determine the types of fungi in the digestive tract of free-range chicken (G. domesticus Linn.). The study was conducted in November 2014 until April 2015 in the Laboratory of Microbiology, Faculty of Mathematics and Natural Sciences, University of Tangjungpura, Pontianak. The isolation of fungi used direct planting method and the identification of fungi based on macro-and micro- morphological characteristics. The results of the study found 13 species of fungi in the free-range chicken digestion tract (G. domesticus Linn.) which taken in oneof the traditional market Pontianak city. Fungi which succefully identified were members of the species Acremonium sp. UH 25, Aspergillus sp. 1 UH 21, A. niger EMP1 U2, A. niger UB1, A. clavatus UH 21, A. nidulans UH 22, Aspergillus sp. 2 UH 24, A. flavus UH 26, A. flavus UB, Penicillium sp. 1UH2 U2, Penicillium sp. 2EMP U2 and also found two types of fungi which were unidentified, sp. 1 UB1 U2 and sp. 2 UB2. The digestion tract section that most commonly found fungi is intestinum tenue with the total 7 typesof fungi.